Association between Herpes Simplex virus type 2 (HSV 2) and bad obstetric outcomes - Hala Mohamed Majeed Hassan; Abdulghani Mohamed Alsamarai; Zainab Khalil Mohamed Aljumaili; Firah Ghali Alsalihi (Our Dermatology Online, 2014)
Introduction: HSV is a common human pathogen that lead to lifelong latent infection. Maternal infections may be associate with transmission to the fetus. The risk factors associated with HSV 2 seropositivity in pregnant women in Iraq are not well studied. Aim: The present study conducted to verify the prevalence of HSV 2 infections in women with bad obstetric history (BOH) in Kirkuk Governorate. Material and Methods: HSV 2 seropositivity among women aged 14 to 48 years was investigated by determination of HSV 2 IgG and IgM in a prospective, case control descriptive study. Results: The overall HSV 2 seroprevalence was 29.9%, with a non significant difference between women with BOH and women with normal pregnancy. HSV 2 IgM, as an indicator of current infection was demonstrated in 2% of the studied population, and was significantly (P=0.002) higher in women with BOH compared to women with normal pregnancy. Both HSV 2 IgG and IgM were significantly varied with age groups, with trends of increasing with older ages. HSV 2 IgG was statistically significantly higher in working women (P=0.03) as compared to housewife. Conclusions: Significant association was found between HSV 2 seroprevalence and education levels, residence, smoking and animal exposure. Presence of pregnancy in women with HSV-2 latent infection was a risk factor for development of BOH.